Sono-electro-magnetic therapy for treating chronic pelvic pain syndrome in men: a randomized, placebo-controlled, double-blind trial. - Thomas M Kessler; Livio Mordasini; Christian Weisstanner; Peter Jüni; Bruno R da Costa; Roland Wiest; George N Thalmann (PLoS ONE)
Objective To assess the efficacy and safety of sono-electro-magnetic therapy compared to placebo in men with refractory CPPS. Patients and methods In a randomized, placebo-controlled, double-blind single center trial, we assessed the effect of sono-electro-magnetic therapy in men with treatment refractory CPPS. Sixty male patients were randomly assigned to treatment with either sono-electro-magnetic (n = 30) or placebo therapy (n = 30) for 12 weeks. The primary outcome was a change in the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) from baseline to 12 weeks. Results The 12-week difference between sono-electro-magnetic and placebo therapy in changes of the NIH-CPSI total score was -3.1 points (95% CI -6.8 to 0.6, p = 0.11). In secondary comparisons of NIH-CPSI sub-scores, we found differences between groups most pronounced for the quality-of-life sub-score (difference at 12 weeks -1.6, 95% CI -2.8 to -0.4, p = 0.015). In stratified analyses, the benefit of sono-electro-magnetic therapy appeared more pronounced among patients who had a symptom duration of 12 months or less (difference in NIH-CPSI total score -8.3, 95% CI -14.5 to 2.6) than in patients with a longer symptom duration (-0.8, 95% CI -4.6 to 3.1; p for interaction = 0.023). Conclusions Sono-electro-magnetic therapy did not result in a significant improvement of symptoms in the overall cohort of treatment refractory CPPS patients compared to placebo treatment. Subgroup analysis indicates, however, that patients with a symptom-duration of 12 months or less may benefit from sono-electro-magnetic therapy, warranting larger randomized controlled trials in this subpopulation. Trial registration ClinicalTrials.gov NCT00688506.